Penguatan Pemahaman Siswa Mengenai Masalah Perekonomian Dan Kebijakan Ekonomi Pada Siswa SMA Negeri 16 Samarinda: Penelitian - Indarto, Seto; Noredyo Molyaningrum; Samuel Marbun (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Understanding economic issues and economic policies is an essential competency for students as the next generation, particularly amid increasingly complex national and global economic dynamics. However, students’ comprehension of these issues remains limited, necessitating structured reinforcement through targeted learning activities. This Community Service Program (PKM) aims to enhance the understanding of students from SMA Negeri 16 Samarinda regarding economic problems and economic policies through an extracurricular science program in the field of economics, in collaboration with IKIP PGRI Kalimantan Timur. The activity was carried out using lecture and discussion methods for 90 minutes, involving seven students participating in the extracurricular program. The material, delivered by a resource person from the Economics Education Study Program, covered fundamental concepts of economic problems, scarcity, economic choice, as well as fiscal and monetary policies. Evaluation results indicate an improvement in students’ understanding by 10%, based on the comparison between pre-test and post-test scores, with the average increasing from 70 to 77. Participants also demonstrated high enthusiasm throughout the activity, as reflected in their active engagement during discussions and their ability to respond to questions related to basic economic concepts. Overall, this PKM activity made a positive contribution to increasing students’ knowledge of relevant economic issues and is expected to strengthen their ability to understand economic policy dynamics in the future.